PERLINDUNGAN HUKUM LAHAN PERTANIAN DALAM PELAKSANAAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM BERDASARKAN UNDANG-UNDANG NOMOR 41 TAHUN 2009 TENTANG PERLINDUNGAN LAHAN PANGAN BERKELANJUTAN (Studi di Kecamatan Pakis Kabupaten Malang) - Firmansyah Abdul Aziz (Dinamika, 2021)
ABSTRACT            The development of the era has encouraged Indonesia to build infrastructure that causes agricultural land to function due to land acquisition for public purposes. Pakis Subdistrict, Malang Regency, is one of the agricultural areas affected by conversion to the public interest. The purpose of this study was to determine the legal protection of agricultural land affected by land acquisition based on Law Number 41 of 2009 in Pakis District and to determine the barriers to implementing its protection, as well as to determine efforts to overcome obstacles in providing legal protection for agricultural land. The research method used is a juridical empirical type through a juridical sociological approach with qualitative descriptive data analysis techniques. The protection of agricultural land in Pakis District, according to the researcher, is divided into two, namely preventive and repressive. The implementation of agricultural land protection in its implementation has encountered several inhibiting factors, namely economic and policy factors. Efforts made in overcoming the obstacles by Regional Regulation Number 6 of 2015 which regulates the Protection of Sustainable Agricultural Land in Malang Regency, however, the implementation has not been effective.Keywords: Legal Protection, Agricultural Land, Land Acquisition ABSTRAK            Berkembangnya zaman mendorong Indonesia membangun sarana prasarana yang menyebabkan lahan pertanian beralihfungsi dikarenakan pengadaan tanah untuk kepentingan umum. Kecamatan Pakis Kabupaten Malang merupakan salah satu daerah pertanian yang terdampak alihfungsi untuk kepentingan umum. Tujuan penelitian ini untuk mengetahui perlindungan hukum lahan pertanian yang terkena pengadaan tanah berdasarkan Undang-undang Nomor 41 tahun 2009 di Kecamatan Pakis dan untuk mengetahui hambatan pelaksanaan perlindungannya, serta untuk mengetahui upaya mengatasi hambatan dalam memberikan perlindungan hukum terhadap lahan pertanian tersebut. Metode penelitian yang digunakan berjenis yuridis empiris melalui pendekatan yuridis sosilogis dengan teknik analisis data deskriptif kualitatif. Perlindungan lahan   pertanian di   Kecamatan   Pakis menurutPeneliti dibagi menjadi dua yaitu prefentif dan represif. Pelaksanaan Perlindungan Lahan pertanian dalam pelaksanaannya menemui beberapa faktor penghamba yakni Faktor Ekonomi dan Kebijakan. Upaya yang dilakukan dalam mengatasi hambatannya dengan Peraturan Daerah Nomor 6 Tahun 2015 yang mengatur tentang Perlindungan Lahan Pertanian Berkelanjutan Kabupaten Malang, namun dalam implementasinya belum efektif.Kata kunci: Perlindungan Hukum, Lahan Pertanian, Pengadaan Tanah